The Relationship between Reproductive Hormones, MFG-E8, and Chlamydial Infection in Infertile Women - Sh Abd Hasan; E Ali Hussein; I Talib Hassan (Majallah-i Dānishgāh-i ̒Ulūm-i Pizishkī-i Bābul)
Background and Objective: Chlamydia trachomatis (CT) is a common sexually transmitted infection that is often symptomless and can cause long-term complications, including infertility. The objective of this study is to evaluate the relationship between reproductive hormones, MFG-E8 (Milk Fat Globule-Epidermal Growth Factor 8), and chlamydial infection in infertile women. Methods: This cross-sectional study was conducted in Al-Salama Hospital between November 2021 and February 2023 on 90 participants, 60 infertile patients and 30 fertile individuals as a control group. The participants were divided into four groups based on their chlamydial infection status and serum levels of CT Ig-G, MFG-E8, AMH (Anti-Müllerian Hormone), LH (Luteinizing Hormone), and FSH (Follicle-Stimulating Hormone), Prolactin, and Testosterone were measured and compared using the ELISA technique. Findings: A notable difference in Ig-G levels was observed based on chlamydia trachomatis infection status of female participants. The infertile group demonstrated significantly higher Ig-G levels, with a mean of 17.22±6.43 in the presence of positive Chlamydial infection, compared to the other groups (p<0.0001). In addition, the mean level of MFG-8 in the fertile group with chlamydia positive, at 215.65±26.07 ng/ml, was significantly higher compared to other groups (p<0.0001). No statistically significant difference was observed in MFG-E8 level between fertile and infertile patients. Conclusion: The results of the study revealed a significant link between chlamydia trachomatis infection and infertility. The fertile women with Chlamydia-positive cases exhibited elevated levels of MFG-8, suggesting its potential involvement in reproductive health. These findings contribute to our understanding of the complex relationship between Chlamydia trachomatis infection, reproductive hormones, and infertility.